1988
DOI: 10.1152/jappl.1988.65.5.2124
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic influence on upper airway patency

Abstract: Patency of the upper airway (UA) is usually considered to be maintained by the activity of muscles in the head and neck. These include cervical muscles that provide caudal traction on the UA. The thorax also applies caudal traction to the UA. To observe whether this thoracic traction can also improve UA patency, we measured resistance of the UA (RUA) during breathing in the presence and absence of UA muscle activity. Fifteen anesthetized dogs breathed through tracheostomy tubes. RUA was calculated from the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
186
1
5

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(196 citation statements)
references
References 0 publications
4
186
1
5
Order By: Relevance
“…These findings suggest that structural alterations predispose to upper airway obstruction during sleep when neuromuscular activity wanes (71). In further studies, investigators have demonstrated that structural defects may arise from soft tissues that compress the pharynx (72-75) and/or a loss of caudal traction on the upper airway from mediastinal, ribcage, and muscle attachments (63,74,76,77).…”
Section: Obesity and Upper Airway Neuromechanical Control Modeling Upmentioning
confidence: 99%
“…These findings suggest that structural alterations predispose to upper airway obstruction during sleep when neuromuscular activity wanes (71). In further studies, investigators have demonstrated that structural defects may arise from soft tissues that compress the pharynx (72-75) and/or a loss of caudal traction on the upper airway from mediastinal, ribcage, and muscle attachments (63,74,76,77).…”
Section: Obesity and Upper Airway Neuromechanical Control Modeling Upmentioning
confidence: 99%
“…For instance, increased compliance and hyperinflation from COPD may reduce the severity of OSAS by increasing the traction on the upper airway and reducing its collapsibility. 3,4 In contrast, an increase in lower airway resistance may increase the negative inspiratory pressure and promote obstructive sleep apnea. We therefore sought to study patients with the overlap of COPD and OSAS to assess primarily the potential association and directionality of the association between the expiratory time constant (as obtained from the nasal pressure signal during polysomnography) and the AHI, and secondarily whether the time constant differs across sleep stages from variations of lung volumes and airway resistance.…”
Section: 2mentioning
confidence: 99%
“…1 PAP tedavisi üst hava yolunu açarak 1 akciğer volümle-rini (fonksiyonel rezidüel kapasiteyi) artırıp, üst hava yolları kaslarının refleks dilatasyonu ve trakeal gerilmeyi sağlar, böylece üst solunum yollarındaki ödemi gidererek etkili olur. 2, 3 OUAS, erişkin popülasyonun %2-4'ünü etkilemektedir. Uyku ile ilişkili solunum bozuklukları hava yolunun tam veya kısmi oklüzyonu ile karakterizedir.…”
Section: Gi̇ri̇ş Ve Amaçunclassified